AF-6 Protects Against Dopaminergic Dysfunction and Mitochondrial Abnormalities in Drosophila Models of Parkinson’s Disease - Basil, Adeline H.; Sim, Joan P. L.; Lim, Grace G. Y.; Lin, Shuping; Chan, Hui Ying; Engelender, Simone; Lim, Kah-Leong (Frontiers in Cellular Neuroscience, 2017)
Afadin 6 (AF-6) is an F-actin binding multidomain-containing scaffolding protein that is known for its function in cell-cell adhesion. Interestingly, besides this well documented role, we recently found that AF-6 is a Parkin-interacting protein that augments Parkin/PINK1-mediated mitophagy. Notably, mutations in Parkin and PINK1 are causative of recessively inherited forms of Parkinson’s disease (PD) and aberrant mitochondrial homeostasis is thought to underlie PD pathogenesis. Given the novel role of AF-6 in mitochondrial quality control, we hypothesized that AF-6 overexpression may be beneficial to PD. Using the Drosophila melanogaster as a model system, we demonstrate in this study that transgenic overexpression of human AF-6 in parkin and also pink1 null flies rescues their mitochondrial pathology and associated locomotion deficit, which results in their improved survival over time. Similarly, AF-6 overexpression also ameliorates the pathological phenotypes in flies expressing the Leucine Rich Repeat Kinase 2 (LRRK2) G2019S mutant, a mutation that is associated with dominantly-inherited PD cases in humans. Conversely, when endogenous AF-6 expression is silenced, it aggravates the disease phenotypes of LRRK2 mutant flies. Aside from these genetic models, we also found that AF-6 overexpression is protective against the loss of dopaminergic neurons in flies treated with rotenone, a mitochondrial complex I inhibitor commonly used to generate animal models of PD. Taken together, our results demonstrate that AF-6 protects against dopaminergic dysfunction and mitochondrial abnormalities in multiple Drosophila genetic models of PD, and suggest the therapeutic value of AF-6-related pathways in mitigating PD pathogenesis.